Estimating Hedonic Demand Parameters with Single Market Data: The Problems Caused by Unobserved Tastes - Bartik, Timothy J. (The Review of Economics and Statistics, 1987)
Timothy J. Bartik, Estimating Hedonic Demand Parameters with Single Market Data: The Problems Caused by Unobserved Tastes, The Review of Economics and Statistics, Vol. 69, No. 1 (Feb., 1987), pp. 178-180